Outcomes of ophthalmology telemedicine in a large health care system beyond initial pandemic crisis - Elaine I. Wu; Mary Reed; Bradley Frueh; Weilu Wu; H. Jane Kim (Heliyon)
Purpose: To compare the outcome of telemedicine versus in-person visit in a large health care system. Design: Retrospective cohort study. Methods: 174,245 patients with a telemedicine or in-person visit from September 2020 to June 2021 in the Kaiser Permanente Northern California Health Care System were included. Main outcome measures were whether an initial telemedicine or in-person visit required a subsequent in-person visit and patient characteristics that differed between telemedicine and in-person groups. Charts of selected televisits with return in-person visits were reviewed for diagnostic accuracy of telemedicine. Results: 27 % of patients who had telemedicine visit had a subsequent in-person visit compared to 13 % of patients who had initial in-person visit. Telemedicine visit was associated with higher risk of needing a subsequent in-person visit compared to an initial in-person visit (RR 2.35, CI 2.30–2.40). Patient characteristics associated with higher risk of telemedicine visit compared to in-person visit included female gender (RR 1.07, CI 1.05–1.08), Asian/Black/Hispanic/other race (RRAsian 1.06, CI 1.04–1.08; RRBlack 1.07, CI 1.04–1.11; RRHispanic 1.03, CI 1.02–1.05; RROther 1.04, CI 1.03–1.06), and English language preference (RR 1.08, CI 1.04–1.11). Age had bimodal distribution with patients younger than 18 and 65 and older associated with less usage of telemedicine. Diagnostic accuracy of telemedicine was 93 %. Conclusions: Although telemedicine visit was associated with higher risk of needing return in-person visits, telemedicine was able to address ophthalmic needs in majority of patients with high diagnostic accuracy. This large health care system study supports the continued used of telemedicine in ophthalmology in post pandemic setting.